Correlation Between Diabetic Cognitive Impairment and Diabetic Retinopathy in Patients With T2DM by 1H-MRS - Lu, Xuefang; Gong, Wei; Wen, Zhi; Hu, Lanhua; Peng, Zhoufeng; Zha, Yunfei (Frontiers in Neurology, 2019)
Objective: To explore the correlation between diabetic cognitive impairment(DCI) and diabetic retinopathy (DR) through examining the cognitive function and the metabolism of the cerebrum in T2DM by 1H-MRS. Methods: 53 patients with T2DM were enrolled for this study. According to the fundus examination, the patients were divided into DR group (n=26) and T2DM without DR group (T2DM group, n=27). 30 healthy adults were selected as a control group (HC group, n=30). The cognitive function was measured by Montreal Cognitive Assessment (MoCA). The peak areas of N-acetylaspartate (NAA), Cho-line (Cho), Creatine (Cr) and Myo-inositol (mI), and their ratios were detected by proton magnetic resonance spectroscopy (1H-MRS). The difference analysis between the three groups was performed by one-way ANOVA. When p<0.05, LSD-t was applied. A partial correlation analysis (with age as a covariate) was used to analyze the correlation between metabolites in the DR group and MoCA scores. Among all T2DM patients, Chi-square test age, gender, education level, BMI, SBP, DBP, FPG, HbA1c, TC, TG, HDL-C, LDL-C, DR, and DCI correlation. Differences were statistically significant while P＜0.05. Results: 1. The scores of MoCA in the DR group or in the T2DM group were significant less than that in the HC group (F=3.54, P<0.05), and the scores of MoCA in the DR group were significant less than that in the other groups (F=3.61, P<0.05). 2. There were significant differences of NAA on bilateral hippocampus in DR patients ,T2DM patients and healthy controls(P＜0.05). 3. The NAA/Cr is significant positive correlated with the score of MoCA in DR patients’ left hippocampus (r=0.781, P＜0.01). 4. Chi-square analysis found that there was a correlation between DR and DCI (x2=4.6, df=1,p=0.032, plt:0.05). There was no correlation between other influencing factors and DCI (P>0.05). Conclusion: DCI is closely correlated with the DR in patients with T2DM. The hippocampal brain metabolism may have some changes in two sides of NAA in patients with DR, 1H-MRS may provide effective imaging strategies and methods to early diagnosis brain damage and quantitative assessment cognitive function in T2DM.